Manzil verses and tranquilizing effect in opiate dependents - Samhani, Ismail; Nasir, Mohamad; Rohayah, Husain; Syed Hadzrullathfi, Syed Omar (2019)
This review article discusses the practicality of Manzil Verses recitation in managing opiate dependency among drug users. Opiate addiction is an alarming public health issue and leads to a variety of social problems such as communicable diseases, financial burden and defects in cognition and behaviors. Drug treatment and rehabilitation in Malaysia is implemented under the purview of the National Drug Agency and the Prison Department, Ministry of Home Affairs. Scientifically, the Manzil Verses act as a form of rhythmic therapy by calming the senses, cognition and palpitations. Thus, this article aimed to discuss the potential of Manzil Verses in terms of their tranquilization effect among those with opiate addiction.